Analyzing instantaneous frequency characteristics of various features in water pipelines via the hilbert transform method - Nor Azinee, Said; Mohd Fairusham, Ghazali; Mohd Fadhlan, Mohd Yusof; Muhammad Aminuddin, Pi Remli; Muhammad Hanafi, Yusop (Semarak Ilmu Publishing, 2025)
Non-revenue water (NRW), caused by water loss in distribution systems, poses a significant challenge to water utilities, particularly in developing nations. Addressing this issue is crucial for financial stability and operational efficiency. This research focuses on applying the empirical mode decomposition (EMD) with the Hilbert transform (HT) method for time-frequency analysis of transient pressure waves in pipeline systems. A transient signal is observed when there is a sudden change in pressure within a pipeline caused by a surge in pressure or the act of opening and closing a valve. The decomposition method is utilized to analyze the transient signal and eliminate the presence of noise that interferes with the signal. This paper presents an approach to investigate the behavior signal of different features in water pipelines. The proposed method combines empirical mode decomposition with Hilbert transform, offering an effective solution. In order to verify the efficacy of the EMD-HT presented in this paper, laboratory experimental tests were done on pipeline systems exhibiting various features, such as leakage, elbow, and junction. The finding shows that the proposed methodology can identify distinct characteristics of various pipe features in water pipelines.